PENERAPAN TRANSFORMASI DIGITAL PADA PELAYANAN PUBLIK DI BADAN PENGELOLA KEUANGAN PROVINSI BENGKULU - NOVLIZA EKA PATRISIA; Faizal Anwar; Astri Dwi S (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2021)
The purpose of this article is to describe the application of digital transformation in data management for public services at the Bengkulu Province Regional Financial Management Agency in order to carry out public services. The results confirm that the application of digital transformation in data management for public services at the Bengkulu Province Financial Management Agency has been carried out well through programs and applications that are in accordance with the internal licensing service data structure. However, data management employees still need assistance by software developers. In addition, the application of digital transformation in data management still needs to be developed so that it can experience improvement in terms of coordination and cooperation with other related agencies externally